REORIENTASI TEOLOGI ISLAM DALAM KONTEKS PLURALISME BERAGAMA - Mustafa, Muhtadin Dg. (Institut Agama Islam Negeri (IAIN) Palu, 2006)
This article tries to elaborate Islamic theological reorientation in the context of religious pluralism employing normative, dialogical, and convergent theology. In other words, howÂ these three approaches can be employed to attack the religious problems encountered by each of religious adherent. Theological-normative approach is intended to declare that religious teachings are absolute truths to respect. Dialogical theology is intended to declare that there should be aÂ dialogue amongst the different religious adherents. In the mean time, convergentive theology is intended to build a good religious understanding and a harmonious religious attitude.Â Kata Kunci : Teologi Islam, pluralisme agama, teologi normative, teologi dialogis, teologi konvergentif